The Effect Of Brand Image On Customer Satisfaction Through Quality Of Courier Services During The Covid-19 Pandemic In Indonesia (SAP Express Depok Case Study) - Maftuchach, Viniyati; Kusnuranti, Aliefia Liza (IJOSMAS, 2021)
Customer satisfaction is important for business continuity, because satisfied customers will reuse the products or services sold, so that the factors that determine customer satisfaction, such as brand image and service quality are always interesting to study. The purpose of this study was to examine the effect of brand image on customer satisfaction through the quality of service delivery SAP Express Depok Branch. The population used in this study were customers who used SAP Express services during the pandemic. The sampling technique used in this research is purposive sampling. The number of samples taken as many as 140 respondents. The type of data in this study is primary data with quantitative research methods to find the direct effect of each variable. Analysis of the data used is the analysis of Structural Equation Modeling (SEM) with the Smart PLS 3.2 program. The test results conclude that Brand Image has a positive and significant effect on customer satisfaction, Brand Image has a positive and significant effect on service quality, Service Quality has a positive and significant effect on customer satisfaction, and Brand Image has a positive and significant effect on satisfaction through service quality. Based on the results of the study, it is necessary to improve the brand image by introducing the SAP Express name more massively, through advertising, holding promotions, and always innovating in good delivery services in terms of speed, security, and convenience of the goods to be delivered.